Energy Consumption of Workers in the Palm Fruit Calcium Inspection Process by Wearing Masks to Go Up and Down Stairs during the Pandemic - Agustina Hotma Uli Tumanggor; Cynthia Eka Fayuning Tjomiadi; Madschen Sia Mei Ol Siska Selvija Tambun (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2022)
The increase in the use of masks during this pandemic has greatly affected work. Wearing mask cuases difficulty in breathing when workers do their work by going up and down stairs. Workers are required to wear masks when checking calcium in reservoirs with the height of about 5 to 10 meters from the ground level at PT. Wijaya Borneo Tiganna. The purpose of this study was to identify the energy consumption of workers wearing masks in working up and down stairs during a pandemic. The method used was Cardiovascular Load (%CVL) and energy consumption of workers before and after wearing masks when going up and down stairs. The results of the study obtained that the %CVL value was 38.37% and was included in the level of need for improvement. The average energy consumption of 3.31 Kcal/minute is included in the light category.